TRANSFORMASI DIGITAL DALAM ORGANISASI: STRATEGI, RESIKO, DAN INOVASI - Anang Bambang Pujianto; Johnson Sinaga; Agung Pramayuda; Mugi Puspita; Irfan Achmad musadat; Muhammad Ghazy Khairi Azka (Universitas Mataram, 2026)
The development of digital technology has transformed the way organizations operate, interact, and adapt to an increasingly dynamic environment. Digital transformation is no longer merely an option but a strategic necessity for organizations to remain relevant and competitive. However, many organizations in Indonesia—particularly educational institutions, MSMEs, and community organizations—still face challenges such as limited digital literacy, the absence of well-defined strategies, and a lack of understanding regarding digital risks. These conditions underlie the implementation of a Community Service (PkM) program with the theme “Digital Transformation in Organizations: Strategy, Risk, and Innovation.” The purpose of this program is to provide comprehensive insights to target partners—namely educators, MSME actors, and non-profit managers—on digitalization strategies, risk management, and innovations applicable to their organizational context. The implementation method was carried out through a national webinar that enabled broad participation from across Indonesia, with activities designed to include material presentations, interactive discussions, and evaluations using questionnaires, pre-tests, and post-tests. The results of the program indicated a significant increase in participants’ understanding of the importance of digital roadmaps, awareness of technological risks, and opportunities for digital-based innovation. Participants also demonstrated strong enthusiasm in adopting simple yet relevant technologies, such as digital marketing and cloud-based management. The implication of these results is that digital transformation can be understood and gradually adopted by various types of organizations when provided with appropriate guidance, even with limited resources. Therefore, this PkM initiative is crucial as it not only enhances digital literacy but also encourages organizations in Indonesia to become more adaptive, innovative, and resilient in facing the era of technological disruption.